PENGARUH KOSENTRASI HORMON KINETIN DAN IAA PADA KULTUR JARINGAN TANAMAN MANGROVE (Rhizophora apiculate BL) - Mahadi, Imam; Wulandari, Sri; Kusmedi, Hana Tasya (Universitas Lancang Kuning, 2024)
Mangroves (Rhizophora apiculata) are one of the plants that grow in mangrove forests. The significant degradation of mangrove forests in Indonesia requires effective and efficient rehabilitation efforts. Efforts to provide superior seeds in a short time and in large quantities, one of which is through tissue culture. ZPT (Growth Regulator) Kinetin and IAA in balance can stimulate the morphogenesis process in the explant. This study used a 4×4 factorial randomized complete (RAL) design with 3 replications. The first factor is the concentration of kinetin. 0 mg/L, 1 mg/L, 3 mg/L, and 5 mg/L. The second factor is IAA concentrations of 0 mg/L, 0.5 mg/L, 1 mg/L, and 1.5 mg/L. The parameters observed were explant growth time, explant growth percentage, and bud height. The results showed an interaction with the plant growth time factor, and the best plant growth rate was achieved using the kinetin treatment of 5 mg/L and the IAA treatment of 1.5 mg/L, while the best shoot height factor was found in the kinetin treatment of 5 mg/L. l and IAA 1 mg/L treatment concentrate.